An Analysis of Language Varieties in Karang Taruna Prenduan Sumenep - Evha Nazalatus Saadiyah; Atikatul Himmah Wahyudi; Moh. Fery Wahyudi (Universitas Negeri Surabaya, 2019)
Language and society are two things that can not separate and every society has its own language, not only every society but also in every community has certain language, the language that used by peoples group and that understood by its members of this group is called speech community. This study aims to investigate the kind of language variations and its meaning used in Karang Taruna Prenduan. It employs a qualitative design. The data of the research were collected through observation and interview with the Karang Taruna members with snowball technique. The findings obtained from this research show that Among twelve classification language variation of speech varieties used by the members the community use secret language variation because nobody knows and just the members who know the meaning of language variation in the community. The language variety coming from creative thinking process of the members and also coming spontaneously. Keywords: Speech Community, Language Variation